Mechanical stress regulates bone regulatory gene expression independent of estrogen and vitamin D deficiency in rats. Issue 1 (21st July 2020) - Nepal, Ashwini Kumar; van Essen, Huib W.; van der Veen, Albert J.; van Wieringen, Wessel N.; Stavenuiter, Andrea W. D.; Cayami, Ferdy Kurniawan; Pals, Gerard; Micha, Dimitra; Vanderschueren, Dirk; Lips, Paul; Bravenboer, Nathalie
Abstract: Mechanical stress determines bone mass and structure. It is not known whether mechanical loading affects expression of bone regulatory genes in a combined deficiency of estrogen and vitamin D. We studied the effect of mechanical loading on the messenger RNA (mRNA) expression of bone regulatory genes during vitamin D and/or estrogen deficiency. We performed a single bout in vivo axial loading with 14 N peak load, 2 Hz frequency and 360 cycles in right ulnae of nineteen weeks old female control Wistar rats with or without ovariectomy (OVX), vitamin D deficiency and the combination of OVX and vitamin D deficiency (N = 10/group). Total bone RNA was isolated 6 hours after loading, and mRNA expression was detected of Mepe, Fgf23, Dmp1, Phex, Sost, Col1a1, Cyp27b1, Vdr, and Esr1 . Serum levels of 25(OH)D, 1, 25(OH)2 D and estradiol were also measured at this time point. The effect of loading, vitamin D and estrogen deficiency and their interaction on bone gene expression was tested using a mixed effect model analysis. Mechanical loading significantly increased the mRNA expression of Mepe, and Sost, whereas it decreased the mRNA expression of Fgf23 and Esr1 . Mechanical loading showed a significant interaction with vitamin D deficiency with regard to mRNA expression of Vdr and Esr1 . Mechanical loading affected gene expression of Mepe, Fgf23, Sost, and Esr1 independently of vitamin D or estrogen, indicating that mechanical loading may affect bone turnover even during vitamin D deficiency and after menopause.